Content analysis and audience receptions of online Da'wah on youtube social media - Muhammad Anshar; Asni Djamereng; Muh. Ilham (Penerbit Universiti Kebangsaan Malaysia, 2024)
YouTube social media has provided online da'wah content that the audience can access. This study aimed to analyze (1) the content of online da'wah on YouTube and (2) the audience's reception of online da'wah on social media. This research uses a qualitative approach with content analysis, determining message characteristics and reception analysis to determine the position of audience acceptance of online da'wah messages. The results of the study show that: (1) Online da'wah materials on YouTube social media contain various themes, namely the study of monotheism (Aa Gym Official), Fiqh (Adi Hidayat Official), and ethical issues (Ustadz Abdul Somad Official). The content of da'wah is in accordance with the characteristics of the preacher and the audience's needs; (2) The audience's reception of online da'wah on social media, YouTube is divided into two, namely the dominant position and negotiation, while the opposition is not found. The audience reception is related to the theme of da'wah, the community's needs, and the interactive style between the preacher and the audience. Therefore, the preacher needs to master social media applications, choose the theme of online da'wah according to his needs, and establish a strong relationship with the audience.